Friendship, Conflict, and Children’s Self-Formation in My Soulmate’s Story: A Study of Maria Nikolajeva - Masyfiyah; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the representation of children’s agency and moral transformation in My Soulmate through Maria Nikolajeva’s perspective on child subjectivity. Rather than treating children merely as recipients of moral instruction, the story presents them as active subjects who negotiate identity, build relationships, experience emotional conflict, and learn through their own mistakes. The analysis focuses on Ferlin as the central character whose subjectivity develops through friendship, misunderstanding, self-reflection, and reconciliation. Her relationship with Minda and Ellenia functions as an intersubjective space in which empathy, responsibility, and self-awareness gradually emerge. The conflict over the lost book becomes a crucial narrative moment, revealing that moral growth in children does not arise from abstract advice alone, but from lived emotional experience and the courage to acknowledge wrongdoing. The study also shows that adult figures, such as parents and teachers, do not dominate the resolution of conflict; instead, they provide an ethical environment that allows children’s autonomy to grow. Thus, My Soulmate demonstrates that children’s literature can serve as an aesthetic and ethical medium through which young readers encounter identity formation, relational agency, and moral becoming in ways that are both affectively engaging and culturally grounded.